THE RUSSIAN MODEL OF CONFLICT MANAGEMENT IN SYRIA (Вісник: Міжнародні відносини, 2024)
The article is devoted to the study of the Russian model of conflict management in Syria. The basic elements of this model were identified as well as its relationship to the norms established in the peacekeeping activities of the international community after the end of the "Cold War". In particular the attention was paid the norms established within UN peacekeeping operations. Special attention is paid to the analysis of the Kremlin's negotiation practice in the process of settling the Syrian conflict.
Keywords: Russia, Syrian conflict, mediation, negotiation process, conflict management